Selection and optimization of protein and carbohydrate assays for the characterization of marine biofouling. Issue 17 (22nd April 2020) - Richards, Chloe; O'Connor, Nicole; Jose, Diveena; Barrett, Alan; Regan, Fiona
Abstract : Biofilms comprise a set of microorganisms attached to a surface through extracellular polymeric substances (EPS). Development of reliable analytical assays are valuable in determining the rate of biofilm attachment on surfaces. Abstract : Biological fouling, also called biofouling, is the undesirable formation of organisms on a surface immersed in water. When the exterior surface of an object such as a vessel is submerged in seawater for a prolonged period, micro and macro organisms usually accumulate on the surface. Biofilms are a set of microorganisms attached to a surface through exopolymers they produce, also known as extracellular polymeric substances (EPS). EPS are a mixture of polymers produced by microorganisms such as bacteria in the presence of biomass. EPS are mainly made up of carbohydrates and proteins, but in smaller quantities, they also contain lipids, nucleic acids, and humic substances. Proteins and carbohydrates found in eps can be quantified by using biochemical methods. The Modified Lowry method, BCA method, and Bradford methods are the common biochemical methods used to quantify protein. Anthrone–sulphuric acid and phenol–sulphuric acid are most common methods used to quantify carbohydrate. The Lowry method was determined to be the best method to quantify protein because it has high precision, low error and low limit of detection. Also, it is highly sensitive and reproducible. The anthrone method was determined to be the best method to quantify carbohydrate because it has high precision, low error, low LOQ. Results were confirmed by testing on substrates deployed in the marine environment to allow establishment of a natural biofilm for study.